A 2-year prospective study of injuries and illness in an elite national junior tennis program - O`Connor, S.; Huseyin, O. R.; Whyte, E. F.; Lacey, P. (The Physician and Sportsmedicine, 2020)
Objectives: Injury and illness in elite national tennis programs can limit players` current and future performance. This study aimed to prospectively examine injuries and illnesses in an Irish elite national junior tennis program over 2 years.